2012
DOI: 10.1111/j.1582-4934.2011.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar cation channels mediate protection from cerebellar exitotoxicity by exercise and inheritance

Abstract: Exercise and inherited factors both affect recovery from stroke and head injury, but the underlying mechanisms and interconnections between them are yet unknown. Here, we report that similar cation channels mediate the protective effect of exercise and specific genetic background in a kainate injection model of cerebellar stroke. Microinjection to the cerebellum of the glutamatergic agonist, kainate, creates glutamatergic excito-toxicity characteristic of focal stroke, head injury or alcoholism. Inherited prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Mutations in these two genes are associated with early onset epileptic seizures [ 38 , 39 ]. A third potassium channel gene was Kcnab2 , a gene that codes for the beta subunit of voltage-gated potassium channels and whose over-expression protects neurons from Glu-induced cell damage [ 40 ] while its under-expression impedes associative memory formation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in these two genes are associated with early onset epileptic seizures [ 38 , 39 ]. A third potassium channel gene was Kcnab2 , a gene that codes for the beta subunit of voltage-gated potassium channels and whose over-expression protects neurons from Glu-induced cell damage [ 40 ] while its under-expression impedes associative memory formation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, the major conclusion is that the earlier the exercise intervention is introduced, the better the prognosis for the patients. Studies on the influence of exercise intervention in traumatic brain injury (TBI) provide interesting comparisons because several studies have shown that physical exercise already during the pre-insult, whether mechanical, fluid, or neurotoxic, protects against disorders resulting from neuroinflammation, apoptosis, blood-brain barrier breakdown, excitotoxins, and functional parameters (Ben-Ari et al 2011;Hassett et al 2011;Itoh et al 2011). In each case, the intimate role of the neurotrophin, brain-derived neurotrophic factor (BDNF) linked to neurogenesis, neuronal survival, and neuroreparation in the brain and CNS (Numakawa et al 2010), appears an essential ingredient in the effects of exercise (Macias et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Centrally, the rehabilitative effects of exercise are well documented in models that span stroke to PD to normal aging, 7-10 including in CNS structures that are not considered regenerative, such as substantia nigra and basal ganglia, 30-32 corticostriatal synapses, 33 and cerebellum. 34 …”
Section: Exercise Is Neuroprotective In Humans and Animalsmentioning
confidence: 97%